(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
Research Objectives This study aims to study, discuss Public Service Accountability in Making Motorized Vehicle Number Signs (TNKB) at the SAMSAT Office in Makassar City. This type of research is a type of case study research to collect more on the aspects of the relationship between institutions in fostering street vendors with 4 informants. Data collection techniques by observation, interview, documentation. The results of research conducted at the SAMSAT Office Makassar City. in public service accountability, namely criteria, namely: Procedure, Cost, Duration, Responsiveness, Inhibiting and Supporting Factors. Based on the results of the study shows the accountability of Public Services in Making Motorized Vehicle Number Signs (TNKB) at the Makassar City SAMSAT Office is going well but there are still some that can be handled because the SAMSAT office in Makassar City in making vehicle number signs (TNKB) is accountable according to rules in SAMSAT Makassar City Office.